Factors associated with injecting-related risk behaviors among people who inject drugs: a systematic review and meta-analysis study. Issue 4 (6th July 2020) - Rezaei, Omid; Ghiasvand, Hesam; Higgs, Peter; Noroozi, Alireza; Noroozi, Mehdi; Rezaei, Fatemeh; Armoon, Bahram; Bayani, Azadeh
Abstract: We conducted this systematic review and meta-analysis study to better understand the factors (being drug use, drug type (methamphetamine vs others), sex partner, frequency of injection, homelessness and being HIV positive) associated with injecting-related risk behaviors (lending and/or borrowing already used syringes) among people who inject drugs (PWID). We searched the English language citations in PubMed, Science Direct, Web of Science, and Cochrane electronic databases for previous studies on risk behaviors among PWID. Two independent researchers reviewed all search results, screened for eligibility and extracted data independently. A meta-analysis was conducted with pooled odds ratio and the 95% confidence intervals for factors associated with injecting risk behaviors among PWID. After detailed assessment of the citations, we included 14 studies in our meta-analysis. Binge drug use (OR, 1.39; 95% CI, 1.06–1.71) and drug type (methamphetamine vs. others) (OR, 1.50; 95% CI, 1.22–1.77) were positively associated with the borrowing of already used syringes among PWID. We also found that drug type (OR, 1.39; 95% CI, 1.16–1.64) and homelessness (OR, 1.89; 95% CI, 1.27–2.51) had a positive association with the lending of already used syringes among PWID. Additionally, being HIV positive was negatively associated with the lending of used syringes among PWID (OR, 0.58; 95% CI, 0.37–0.63). This systematic review and meta-analysis supports harm-reduction initiatives especially the establishment and maintenance of sterile needle syringe programs.